Creatinine increase following initiation of antihypertensives is associated with cardiovascular risk: a nationwide cohort study. Issue 12 (December 2020) - Schytz, Philip Andreas; Nissen, Anders Bonde; Torp-Pedersen, Christian; Gislason, Gunnar H.; Nelveg-Kristensen, Karl Emil; Hommel, Kristine; Gerds, Thomas A.; Carlson, Nicholas
Abstract : Objective: Abrupt decline in renal function following initiation of renin–angiotensin system inhibitor is associated with increased risk of cardiovascular disease, but studies of other antihypertensive drugs are sparse. We investigated the risk of cardiovascular event associated with increased plasma creatinine after initiating first-line antihypertensive treatment. Methods: In a nationwide cohort study, we identified adult Danish primary care patients initiating either renin–angiotensin system inhibitor, calcium channel blocker or thiazide, between 2008 and mid-2018. Patients with prior end-stage renal disease, renal transplantation, or cardiovascular disease were excluded. Percentual plasma creatinine increase was calculated between the nearest creatinine measurement up to 1 year before redeeming the prescription (baseline), and the nearest measurement 90 days or less after (index). Multiple logistic regression and restricted cubic splines were applied to estimate the 6-month absolute risk of cardiovascular event (ischemic heart disease, heart failure or stroke) associated with this creatinine increase. Results: We included 20 789 patients. Within the first 6 months of follow-up, 283 (1.4%) cardiovascular events and 93 (0.4%) all-cause deaths were registered. With a creatinine increase of 0 and 30%, 6-month absolute risk [CI] of cardiovascular event was 1.4% [1.1–1.9] and 3.5% [2.4–5.2], respectively (in men aged 50–79 years with estimated glomerular filtration rate at least 60 ml/min per 1.73 m 2 and no diabetes). Higher age and reduced renal function, but not the type of antihypertensive treatment, were associated with higher cardiovascular risk. Conclusion: In primary care, patients initiating first-line antihypertensive treatment, an increase in plasma creatinine above 30% was associated with increased absolute 6-month risk of cardiovascular event. Abstract : Supplemental Digital Content is available in the text